Measurement of tethered swimming force and power for Japanese national water polo players using an electromagnetic brake-type ergometer - Wakayoshi, K.; Akashi, K.; Fukui, T.; Stewart, A. M.; Tachi, M. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
We aimed to establish a simple evaluation method for measuring the tethered swimming force and power in the specific motions required during a water polo game. Fourteen male Japanese national players were asked to perform a maximal effort arm scull with eggbeater kick and frontcrawl stroke with breaststroke kick. An electromagnetic brake-type ergometer acted as a load device to investigate the relationship between tethered load and swimming velocity. The tests of maximum effort swim were performed in four 15 sec work bouts at the load of 0.5, 1.0, 1.5 and 2.0 kp (1kp=92.5 N). From the relationship between the load and the measured velocity, maximum tethered swimming force and power was obtained for each participant. In all participants, a significant correlation was found for the relationship between the load and the velocity. Maximum swimming force for the arm scull with eggbeater kick was higher than that for frontcrawl stroke with breaststroke kick. Furthermore, there were some characteristics in maximum tethered swimming force and power among the positions of the players. Therefore, it is suggested that the method used in this study was effective in evaluating the swimming performance of water polo players.